KONFLIK HUBUNGAN PUSAT-DAERAH antara PEMERINTAH PUSAT DAN KABUPATEN BLORA TERKAIT dengan DANA BAGI HASIL BLOK CEPU - Setiyono, Budi; Satrio Jat, Dio; Jamaludin, Teten (Jurnal Desentralisasi, 2012)
Cepu Block located between Centre Jawa and Easth Java. Its known as a rich block because it has a source of oil and gas. Block Cepu, where geograficaly located between three districs, Blora (Centre Java), Bojonegoro and Tuban (East Java) has given contribution to national budget (APBN) and respected local government budget (APBD). About 33 percent of land of Cepu Block is owned by Blora, 67 percen onwned by Bojonegoro and the rest is owned by Tuban. Ironically, however, although 33 percent of the Block belongs to Blora, the district does not receive any financial income from the oil exploration. There is no resources share fund from Cepu Block. Moreover, the distric has to deal with the negative impacts of exploration activities at the Block Cepu such as damaging of infrastructure, environmental pollution, and social disturbance. Blora Distric have protested to Centre Government, but so far there is no outcomes. Centre Government asked that this problem should be studied first. The central government argue that if it is approved, then there will be domino impact: other districts will do same like Blora. Blora district is struggling to get equality in resources share fund (dana bagi hasil). Efforts have done, seminars and workshops, lobby to DPD (Upper House) to find solution. Now the district government is proposing judicial review to constitution court. This reseach examines the history of Block Cepu. It reveals the history of the block from colonial era up to reformation era. Further, the research aims to know how the tension between local government (Blora Government) and central government regarding Blok Cepu oil exploration. The research suggests that, there is injustice in the distribution of revenue from the exploration and it is understandable if Blora district government struggle to get proportional revenue sharing